Five modes of China's economic influence: rethinking Chinese economic statecraft - Ferchen Matt; Mattlin Mikael (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Interest and anxiety about China's economic statecraft, or the ways in which it uses economic means to achieve foreign policy, is booming. The overriding perception is that China has sophisticated, long-term plans to enhance its power on the global stage through the use of economic strategies and tools and that it is uniquely capable of effectively implementing those plans now or in the future. Yet when it comes to actual outcomes, whether or not China has been able to achieve its foreign policy goals via economic means, the evidence is mixed at best. This article seeks to move beyond some of the shortcomings in our understanding of Chinese economic statecraft by exploring the links between perceptions, ambitions, abilities, and outcomes of Chinese foreign economic policies and behaviour. We propose an alternative to the concept of economic statecraft by introducing instead five different 'modes of economic influence'. We suggest directions for future research focused on China's economic influence, including its latent structural power.